Imagining karma : ethical transformation in Amerindian, Buddhist, and Greek rebirth - Obeyesekere, Gananath (Berkeley : University of California Press, 2002)
With 'Imagining Karma', Gananath Obeyesekere embarks on the comparison of rebirth concepts across a wide range of cultures. The book makes a case for disciplined comparison, a humane view of human nature, and a theoretical understanding of 'family resemblances' and differences across great cultural divides.
Illustrations; Preface; Abbreviations; 1 Karma and Rebirth in Indic Religions: Origins and Transformations; 2 Non-Indic Theories of Rebirth; 3 The Imaginary Experiment and the Buddhist Implications; 4 The Buddhist Ascesis; 5 Eschatology and Soteriology in Greek Rebirth; 6 Rebirth and Reason; 7 Imprisoning Frames and Open Debates: Trobriander, Buddhist, and Balinese Rebirth Revisited; Notes; Bibliography; Index.
Includes bibliographical references (pages 413-427) and index.
Print version record.
JSTOR
Keywords: Reincarnation -- Buddhism; Reincarnation -- Comparative studies; Religious ethics -- Comparative studies; Réincarnation -- Bouddhisme; Réincarnation -- Études comparatives; Morale religieuse -- Études comparatives; RELIGION -- Comparative Religion; RELIGION -- Buddhism -- General; Reincarnation; Reincarnation -- Buddhism; Religious ethics; Reïncarnatie.; Vergelijkend onderzoek; amerindian tradition; buddhism; buddhist tradition; canada; classicists; cosmology; cross cultural scholarship; cultural relativism; cultural stories; death; empedocles; ethics; greek tradition; human condition; indic civilizations; indologists; intellectual context; karma; melanesia; methodological framework; nietzsche; personal transformation; philosophy; pindar; plato; pythagoras; rebirth; reincarnation; siberia; textbooks; weber; west africa; wittgenstein; Comparative studies